Functional constipation in children; changing clinical spectrum with unusual presentation: A case report (Indian Journal of Case Reports, 2019)
Constipation in children is progressively increasing day by day because of changing lifestyle and dietary intake. Sometimes, functional constipation cases are misdiagnosed as functional abdominal pain because of inappropriate history and examination. We present an 8-years-old boy with a history of intermittent moderate to severe abdominal pain for 2 months. Basic blood investigations and ultrasound of the abdomen were normal, surprisingly, X-ray of the abdomen revealed the diagnosis. Simple X-ray erect abdomen is very useful in a special situation for the diagnosis of functional constipation.